Women Village Facilitator Action on Economic Revitalization of the Women's Group: a Case Study in 3 peatland villages, Central Kalimantan - Subono, Nur Iman; Pratiwi, Andi Misbahul; Boangmanalu, Abby Gina (Yayasan Jurnal Perempuan, 2020)
Peatlands play an important role in the ecological and economic aspects. Peatlands degradation in various regions in Indonesia brings economic issues, especially for women. The involvement of women in the peatland restoration program as a strategy needs to be reviewed. This research focuses on the involvement of women in the peatland restoration as a village facilitator, mainly on aspects of economic revitalization. This research focuses in 3 Villages in Central Kalimantan Province, Jabiren Village, Tumpang Nusa Village, and Gandang Barat Village. The main question of this research is how are the actions, challenges, and strategies experienced by women as village facilitators in the Desa Peduli Gambut program. Based on in-depth interviews with relevant actors and literature studies, this research finds, 1) the economic revitalization program conducted by women village facilitators build the economic resilience of rural women communities and changes the gender relations; 2) women village facilitators faced structural and cultural obstacles in their action; 3) the program is also the part of political actions for peatlands preservation.